TECHNOLOGY’S IMPACT ON THE EDUCATION PROCESS - Rustamova , Shahnoza Aripovna; Juraeva , Shakhlo Dilshod qizi (Educational Research in Universal Sciences, 2023)
This literature review aims to explore and analyze the importance of technology in the learning process. The progress of technology in education has transformed the way students learn and mentors teach. Through an extensive review of research articles, this paper highlights the positive impact of technology on student engagement, motivation, information retrieval, and collaboration. Additionally, it addresses the challenges and potential drawbacks associated with technology integration, offering recommendations for effective implementation. Ultimately, this review emphasizes the essential role that technology plays in enhancing the educational experience and preparing students for the digital age.